STRATEGY OF DEVELOPMENT AND MANAGEMENT OF DIGITAL LIBRARY IN IMPROVING STUDENT LITERACY CULTURE UIN SYARIF HIDAYATULLAH JAKARTA - Ginanjar, Muhammad Hidayat; Mutaal, Ijaz; Ulum, Aldi Bahrul; Sayaf, Muqorobin Umar; Hidayat, Rifqi (Islamic Management: Jurnal Manajemen Pendidikan Islam, 2024)
This research to determine the strategy for developing and managing digital libraries in improving students' literacy culture and the various problems they face. This study uses a qualitative approach with descriptive analysis. Data collection techniques are by conducting observations, interviews and document studies. The results of this study suggest, among others: (1) The UIN Syarif Hidatullah Jakarta Library has not implemented a comprehensive digital system and is still in the development stage to switch to digital which is called the Hybrid Library.; (2) The lack of digital book collections and lack of socialization are the main leaders of the UIN Jakarta library in managing digital libraries. The solution is to collaborate with several international journal parties. Other factors that are leaders are budget limitations, storage limitations, and obstacles to the procurement of electronic goods.; (3) the use of digital collections owned by the UIN Jakarta Library is less than its non-digital collections.